Beyond Natural Resources to Post-Human Resources : Towards a New Theory of Diversity and Discontinuity. - Baofu, Peter (Cambridge Scholars Publishing, 2013)
Are natural resources really so limited that, as Mahatma Gandhi once famously said, ""Earth provides enough to satisfy every man's need, but not every man's greed""? (TE 2012) This limiting view of natural resources can be contrasted with an opposing view by John Maynard Keynes, who ""summarized Say's Law as 'supply creates its own demand'"" but then ""turned Say's Law on its head in the 1930s by declaring that demand creates its own supply, "" so whenever a demand exists, there will be resources t ...